Viscoelastic droplet impact on surface - Ho, Yenn Shen (2018)
This report investigates the viscoelastic effect on the spreading of droplet after impacting on a dry surface through the using of high-speed imaging techniques (SA-X2, Photron). Different viscoelastic fluids were used by adding PEO (Sigma Aldrich) of varying molecular weight and concentration to distilled water. The impact behaviour of the droplets was observed and analysed using the spreading images captured by the camera. Spreading diameter of Newtonian and non-Newtonian (viscoelastic) droplets were obtained to find out the effect of varying molecular weight and concentration on the maximum spreading diameter. From the analysis, an increase in molecular weight and/or concentration of the viscoelastic droplets resulted in smaller maximum spreading diameters. From this understanding, attempts were made to scale the spread factor of the sample solutions to a single characteristic curve to obtain a prediction model for the maximum spreading diameter of viscoelastic fluid.